Upaya Pemerintah Desa Teru Dalam Menangani Masalah Pemberhentian Hubungan Kerja Pasca Pandemi Covid-19 Di Desa Teru - Pawari, Rahmiati Ranti (Universitas Sang Bumi Ruwa Jurai, 2024)
During the Covid-19 pandemic, many workers in Indonesia had to be laid off and even had their employment terminated. This is also experienced by the community in Teru Village, Simpang Katis District, Bangka Regency. The government has made various efforts to overcome this, starting from implementing pre-employment cards, BLT, social assistance for MSMEs, and so on. The method used in this research is a normative legal research method, namely research on library materials that are relevant to the problem to be analyzed, whether in the form of primary legal materials, secondary legal materials, or tertiary legal materials. The research results concluded that the Teru Village Government took strategic steps to help residents affected by the Covid 19 pandemic by allocating funds from the APBDes, in collaboration with the Bangka Regional Government and stakeholders